Multiple resections and survival of recurrent glioblastoma patients in the temozolomide era. (February 2016) - Ortega, Alicia; Sarmiento, J. Manuel; Ly, Diana; Nuño, Miriam; Mukherjee, Debraj; Black, Keith L.; Patil, Chirag G.
Abstract: Glioblastoma (GBM) is the most prevalent and aggressive primary brain tumor in adults for which recurrence is inevitable and surgical resection is often recommended. We investigated the relationship between multiple tumor resections and overall survival (OS) in adult glioblastoma patients who received adjuvant radiotherapy and temozolomide following initial surgery. We retrospectively reviewed the records of all newly diagnosed adult GBM patients with tumor recurrence at our institution from March 2003 to October 2012. Kaplan–Meier survival estimates and multivariate analysis using Cox's proportional hazards model were utilized to evaluate the impact of multiple resections on OS. A total of 202 GBM patients were analyzed; 83 (41.1%), 94 (46.5%), and 25 (12.4%) patients underwent one, two, and three or more total resections, respectively. Patients who underwent multiple resections were significantly younger ( p < 0.0001) and had higher perioperative Karnofsky Performance Status scores ( p < 0.0001) than single resection patients. The median OS in months was 21.1, 25.5, and 29.0 for patients who had one, two, and three or more resections, respectively (Wilcoxon p = 0.03). In a confounder-adjusted multivariate model, patients with multiple resections did not have significantly improved survival ( p = 0.55). Older age was strongly associated with poorer OS (hazard ratio 1.34, p < 0.0001). Age at diagnosis was the only predictor of survival for recurrent GBM patients. After adjusting for age at diagnosis, multiple resections were not an independent predictor of OS in our glioblastoma cohort treated in the temozolomide era.